2016
DOI: 10.1055/s-0041-110792
|View full text |Cite
|
Sign up to set email alerts
|

Screening primary sclerosing cholangitis and biliary dysplasia with endoscopic retrograde cholangiography and brush cytology: risk factors for biliary neoplasia

Abstract: Even in mostly asymptomatic patients with PSC, 42.9 % had advanced disease and 6.9 % presented with suspicious or malignant brush cytology at first ERC. Advanced extrahepatic ERC changes with elevated aminotransferases at diagnosis might be risk factors for biliary neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 22 publications
2
58
0
Order By: Relevance
“…(97,98) In a recent study performed on 433 PSC patients, 41 of whom had biliary malignancy, the use of FUT2/3 genotypedependent cut-off values for CA19-9 improved sensitivity and reduced the number of false positive results (99). In a study screening for biliary dysplasia using ERCP and brush cytology, serum CA19-9 had no prognostic value for biliary dysplasia or CCA (39). Currently, there are no definite radiologic features that indicate CCA in a PSC patient, although the detection of a DS by MRCP may be suggestive for CCA.…”
Section: Esge/easl Suggest Routine Administration Of Prophylactic mentioning
confidence: 99%
See 1 more Smart Citation
“…(97,98) In a recent study performed on 433 PSC patients, 41 of whom had biliary malignancy, the use of FUT2/3 genotypedependent cut-off values for CA19-9 improved sensitivity and reduced the number of false positive results (99). In a study screening for biliary dysplasia using ERCP and brush cytology, serum CA19-9 had no prognostic value for biliary dysplasia or CCA (39). Currently, there are no definite radiologic features that indicate CCA in a PSC patient, although the detection of a DS by MRCP may be suggestive for CCA.…”
Section: Esge/easl Suggest Routine Administration Of Prophylactic mentioning
confidence: 99%
“…However, the modest sensitivity from bile duct brushing precludes its utility as a diagnostic tool for early detection of CCA in patients with PSC. In a recent study of 261 mostly (81%) asymptomatic patients with PSC referred for their first ERC to confirm diagnosis and screen for biliary dysplasia with systematic bile duct brushings, 43% were found to have advanced disease, and malignant/suspicious cytology was present in 6.9% (39).…”
Section: Brush Cytologymentioning
confidence: 99%
“…However, all patients had some degree of fibrosis or cirrhosis in the histology of the explanted liver. A recent study at our centre reported that 42.9% of mostly asymptomatic patients had advanced disease, and almost 7% presented with suspicious or malignant brush cytology in the first ERC …”
Section: Discussionmentioning
confidence: 99%
“…Low‐grade dysplasia was a significant predictor of both high‐grade dysplasia and CCA. Boyd recently reported increased risk (HR 20.9, P <.001) for biliary neoplasia with suspicious or malignant cytology. In our present study of 35 asymptomatic PSC patients with LTx, dysplasia was observed in 15 explanted livers (42.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation